A new record of Pseudanthias calloura (Perciformes: Anthiadidae) from the central South China Sea, with notes on its osteology and phylogenetic position - Tang, Chi-Ngai; Gill, Anthony C. (Zootaxa, 2026)
During a survey of unidentified anthiadid specimens in the Smithsonian fish collection, we discovered a rare mesophotic anthiadid species, Pseudanthias calloura, originally described from Palau. The species is represented by old material collected in the 1960s from the Macclesfield Bank in the South China Sea (SCS), indicating a broader geographical distribution than previously recognized. Subsequent osteological examinations revealed an unusual predorsal configuration in P. calloura, characterized by a close alignment of the two anteriormost neural spines and the insertion of all supraneurals anterior to the first neural spine. We formally document the occurrence of P. calloura in the SCS and provide a detail description of the species, including previously unreported osteological features based on SCS specimens. Given the widely recognized non-monophyletic nature of Pseudanthias, we also discuss the potential phylogenetic position of P. calloura among its closest relatives. Finally, we review the anthiadid species reported from Macclesfield Bank.